Case report of rare presentation of schistosomiasis: delayed diagnosis of genitourinary schistosomiasis in an adolescent - Valentina Caputo; Cosimo Bleve; Giulia Brooks; Elisa Zolpi; Salvatore Fabio Chiarenza (La Pediatria Medica e Chirurgica)
Schistosomiasis is a tropical infection endemic to developing nations that can result in chronic liver damage, renal failure, infertility, and bladder cancer. Genitourinary localization is marked by dysuria, visible hematuria, and urinary obstruction. We present the case of a 17-year-old male adolescent from a rural area of Central Africa, who arrived in Italy two years prior, exhibiting hematuria and urinary symptoms. He came to our attention with a history of terminal hematuria, dysuria, and intermittent abdominal pain since the age of ten. We conducted initial blood tests, urine analyses, and ultrasonography, all yielding negative results. Cystoscopy was conducted with biopsy of an atypical bladder lesion due to the persistence of hematuria. Histopathology revealed morphological findings indicative of Schistosoma haematobium. The patient received praziquantel treatment and was monitored through parasitological urine analyses. Bladder schistosomiasis should be considered in children exhibiting terminal hematuria from endemic regions. Diagnosis can be established through a urinary microbiological examination. An endoscopic evaluation may assist in the diagnosis if the results are negative.